1992
DOI: 10.1056/nejm199207303270504
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Supraventricular Tachycardia Due to Atrioventricular Nodal Reentry by Radiofrequency Catheter Ablation of Slow-Pathway Conduction

Abstract: Catheter ablation of the atrial end of the slow pathway using radiofrequency current, guided by ASP potentials, can eliminate AVNRT with very little risk of atrioventricular block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
468
5
27

Year Published

1994
1994
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,072 publications
(515 citation statements)
references
References 18 publications
15
468
5
27
Order By: Relevance
“…Nevertheless, disturbances of AV-nodal conductivity are of pathophysiological and clinical relevance, such as in the formation of dual pathways with different conduction velocities (slow and fast conducting areas of the AV node) (31). Different conduction properties of AV-nodal tissue with such division into slow (short refractory period) and fast (long refractory period) pathways facilitate development of local reentry and, thus, are the pathophysiological substrate for AV-nodal reentry tachycardia, the most common congenital supraventricular tachycardia in humans (32,33). Despite the high incidence of this tachycardia, little is known about the ultrastructural and cellular changes of the AV-nodal tissue leading to these differences in conduction velocity.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, disturbances of AV-nodal conductivity are of pathophysiological and clinical relevance, such as in the formation of dual pathways with different conduction velocities (slow and fast conducting areas of the AV node) (31). Different conduction properties of AV-nodal tissue with such division into slow (short refractory period) and fast (long refractory period) pathways facilitate development of local reentry and, thus, are the pathophysiological substrate for AV-nodal reentry tachycardia, the most common congenital supraventricular tachycardia in humans (32,33). Despite the high incidence of this tachycardia, little is known about the ultrastructural and cellular changes of the AV-nodal tissue leading to these differences in conduction velocity.…”
Section: Discussionmentioning
confidence: 99%
“…14 Also, it was shown that RF energy application near the CSOS inferior to the AV node can selectively eliminate the slow pathway conduction. 1,15 In addition, Keim et al 16 demonstrated the location of the site of the antegrade slow pathway using ice mapping techniques. Histological findings in patients also have provided evidence that the AV node itself does not participate in the slow pathway conduction.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, the exact boundaries of the reentry circuit in AVNRT have not been convincingly defined. The purpose of the present study was to define the tachycardia circuit in AVNRT.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Mapping of the cardiac chambers is performed with relatively stiff manually deflectable catheters with unidirectional or bidirectional deflection radius. Steering of those electrodes is performed via a pull-wire mechanism integrated in the handle of the catheter, allowing a reliable and reproducible deflection.…”
mentioning
confidence: 99%